Growth of Si-Doped Polycrystalline Diamond Films on AlN Substrates by Microwave Plasma Chemical Vapor Deposition - Sedov, V.S.; Khomich, A.A.; Ralchenko, V.G.; Martyanov, A.K.; Savin, S.S.; Poklonskaya, O.N.; Trofimov, N.S. (Journal of Coating Science and Technology, 2021)
Microcrystalline diamond films doped with silicon have been grown on aluminum nitride substrates by a microwave plasma CVD. The doping has been performed via adding silane in various concentrations to CH4-H2 reaction gas mixture in course of the deposition process. The films produced at the substrate temperatures of 750 to 950°C have been characterized by SEM, AFM, Raman and photoluminescence (PL) spectroscopy to assess the effect of Si doping on the diamond structure. The doped films showed bright photoluminescence of silicon-vacancy (SiV) color centers at 738 nm wavelength as well as noticeable side band at 723 nm. The optimum doping condition (SiH4/CH4 = 0.6%), that maximize the SiV PL emission, was determined for the range of silane concentrations SiH4/CH4 (0.0 - 0.9%) explored. A further PL enhancement can be achieved by increase in the substrate temperature. The applied in situ doping from gas phase is shown to be an easy and effective method to incorporate Si in diamond in a controllable way.